Systematics of the South American genus Plumarius Philippi, with descriptions of new species (Hymenoptera, Plumariidae) - Diez, Patricia Alejandra (2012)
This contribution presents the study of a first group of species of Plumarius Philippi, 1873, as the result of an extensive survey of the morphological variation present in males. The survey uncovered many useful characters to distinguish between the numerous species of the genus. The studied group consists of Plumarius hirticornis (André, 1909) and the following four new species: Plumarius willinki Fidalgo n. sp., Plumarius filipalpis Roig-Alsina n. sp., Plumarius spiniferus Roig-Alsina n. sp. and Plumarius gradifrons Diez n. sp. A characterisation of the group, descriptions and illustrations are provided. A lectotype is designated for Konowiella hirticornis André, 1909.